Resistência à flexão em porcelana feldspática: efeito da ciclagem mecânica e limite de fadiga pelo método escada - Schalch, Max Von [UNESP]; Chaves, Carolina de Andrade Lima [UNESP]; Medeiros, Flávia Regina [UNESP]; Almeida-Júnior, Antonio Alves [UNESP]; Abi-Rached, Filipe de Oliveira [UNESP]; Cruz, Carlos Alberto dos Santos [UNESP] (My University, 2013)
This study evaluated the fatigue limit (FL) by the staircase method and the effect of mechanical cycling on the flexural strength (FS) of Duceragold feldspathic porcelain. Specimens (25 x 5 x 2 mm) were made according to manufacturer’s directions and submitted to three-point flexural strength test (n = 10). To determine FL (n = 30; 10,000 cycles; 2 Hz), an initial loading of 60% of the FS and an incremental loading (step) of 3% of the FS were used. Data were analyzed by Anova and Tukey´s test (p < 0.05). Although the proposed cycles have not reduced FS significantly, fractography analysis showed striation, characteristic signs of mechanical fatigue.

Este estudo avaliou o limite de fadiga (LF), determinado pelo método escada, e o efeito da ciclagem mecânica sobre a resistência à flexão (RF) da porcelana feldspática Duceragold. Corpos de prova (25 x 5 x 2 mm) foram confeccionados de acordo com as instruções do fabricante e submetidos ao ensaio de RF (n = 10), em três pontos. Para determinação do LF (n = 30), foram utilizados carregamento inicial de 60% da RF, tensão incremental de 3% da RF, 10.000 ciclos e 2 Hz. Os dados foram submetidos à Anova e teste de Tukey (p < 0,05). Embora os ciclos propostos não tenham reduzido estatisticamente a RF, análises fractográficas evidenciaram estrias, sinais característicos de fadiga mecânica
Flexural strength of feldspathic porcelain: effect of mechanical cycling and fatigue limit by the staircase method
Keywords: Dental materials; Dental porcelain; Material resistance; Fatigue; Materiais dentários; Porcelana dentária; Resistência de materiais; Fadiga